ECUADOR’S DECISION TO GRANT ASYLUM TO JULIAN ASSANGE : THE MANIFESTATION OF HUMAN SECURITY? - Kusriyati, Atik (UI Scholars Hub, 2013)
Ecuador’s decision to grant asylum to Julian Assange (Australian citizen) on August 16, 2012 has caused several impacts. Julian Assange, the founder of WikiLeaks, was arrested in Britain in connection with a Swedish investigation into accusations of sexual offenses. But United States Law enforcement official said that the fact that he was in custody did not affect their deliberations about whether he might be charged in this country in connection with publication of leaked government documents. Being disappointed with the decission, the British authorities sent a written notice to the Ecuador’s Embassy in London that they would assault the Embassy if Assange was not handed over. The letter has led to tense diplomatic relations between two countries. Facing the difficult situation, UNASUR (The Union of South America Nations) held a Foreign Ministers Meeting (FMM) after the President of Ecuador granted the asylum. The meeting produced an agreed document that support Ecuador’s decision and encourage all parties to have continous negotiation to find mutually acceptable solutions based on good neighbour principles.